(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article highlights the state of training future engineers, the existing problems studied, Information Theory, Research on the introduction of information and communication technologies in education, the use of intellectual and communicative abilities, the peculiarities of modern multimedia complexes, the promising opportunities for improving the effectiveness of the study of technological processes, as well as the levels of ensuring computer literacy of.